Les quatre phases de la naissance du Nouveau Testament: esquisse d'une historie de la première littérature chrétienne - Theißen, Gerd (Revue d'histoire et de philosophie religieuses, 2007)
In the history of New Testament literature and its forms we can distinguish four phases: in a "charismatic" phase two persons, Jesus and Paul, give rise to the development of two fundamental forms, gospel and letter, which are imitated in a "pseudepigraphic" phase, completed in a "functional" phase by forms that occur only once (Acts, Apocalypse, Hebrews), and collected in a "canonical" phase according to the model of the Septuagint but in contrast with Marcion. The four phases reflect the authority of charisma, tradition, literary genre and the Church. From a form critical point of view, apocryphal Christian literature is a continuation of the functional phase. Early Christian literature is characterised by a dynamics that transcends the boundary between Jews and Gentiles, upper and lower classes, and oral and written traditions. It is literature of a small subculture that pretends to be the beginning of a new mankind.